(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the nutritional status of patients before elective abdominal surgery and the nutritional care provided to these patients. Subjects and methods: A cross-sectional descriptive study was conducted from April 1, 2024, to October 31, 2024, on 40 patients undergoing elective abdominal surgery in the Thai Nguyen National Hospital. Data were collected through interviews using a pre-designed questionnaire, bedside examinations, and secondary data from medical records. Data were processed using SPSS 20.0 software. Results: The group of patients undergoing colon surgery accounted for the highest proportion (60%). The rate of patients experiencing unintentional weight loss within 6 months prior to hospitalization for gastrointestinal surgery was 62.5%. Nutritional screening using the SGA method revealed the highest rate of malnutrition at 50%. During the 24-hour preoperative hospitalization period, the prevention of refeeding syndrome was achieved in only 12.5% of cases. Only 47.5% of patients received intravenous fluids, 25% were given carbohydrate loading the day before surgery, and 17.5% were given carbohydrate loading 2 hours before surgery. Conclusion: The rate of malnutrition or risk of malnutrition in patients before surgery was relatively high at 50%. The prevention of refeeding syndrome was achieved in only 12.5% of cases. Only 17.5% of patients received carbohydrate loading 2 hours before surgery.